Electromagnetic studies of the northern slope of the central part of the Ukrainian Shield - Kushnir, A.N.; Burakhovich, T.K.; Shyrkov, B.I.; Dzhaoshvili, V.B. (Reports of the National Academy of Sciences of Ukraine, 2017)
In 2016, new experimental synchronous observations were carried out with the use of low-frequency electromagnetic methods MTS and MVP in a wide range of periods in the joint zone of the northern slope of the cen tral part of the Ukrainian Shield and Dnieper-Donets Basin. Their primary interpretation indicates the presence of both the near-surface (contact zone of the sedimentary rocks of the Dnieper-Donets Basin and Ukrainian Shield) and deep conducting structures (Kirovograd anomaly in the Earth's crust and southern side of the Dnieper-Donets Basin in the lower part of the crust and/or on the margin with the upper mantle) of different orientations in space. The absence of deep conductivity anomalies in the Earth's crust and the upper mantle in the northern part of the Golovanivsk (Yadlov-Trakhtemirov) suture zone confirms the geodynamic hypothesis of its formation under compression.